Problems in Writing Explanation Text Faced by Third Grade Students of SMAN 1 Barabai - Assifa Yasmin Amini (Hasanuddin University, 2024)
Writing is one of the skills that must be mastered in learning English. The students are likely having difficulty in writing explanation text. Explanation text is important to explore in order to know student’s ability to write nonfictional paragraph. Related to this matter, the purpose of this research is to analyze and describe the students' problems in writing explanation text at SMAN 1 Barabai in third grade. This research is conducted by using questionnaire for students, interview for the teacher and document analysis from student's explanation text writing as supporting instrument to collect data. The results for questionnaire and documents that researcher collected is the researcher found the students have linguistic problem and cognitive problem. Align with another research that explained students’ difficulties in writing explanation text, the results were students’ difficulties in Grammar, Vocabulary, Mechanic, Organization, and Idea or Content. Therefore, the researcher suggests the students need to develop their vocabulary and literacy in order to develop their ability in writing English.